Electrochemical Contact Separation for PVD Aluminum Back Contact Solar Cells. (April 2015) - Kamp, Mathias; Maywald, Axel; Bartsch, Jonas; Efinger, Raphael; Keding, Roman; Glatthaar, Markus; Glunz, Stefan W.; Krossing, Ingo
Abstract: This work deals with a possibility to simplify the processing of back-contact back-junction solar cells. A novel metallization process without using any additional mask is presented. The main focus is set on the contact separation resulting in the interdigitated metal pattern. In case of using evaporated aluminum as contacting material to silicon, aluminum anodizing is a convenient process to convert electrically conductive aluminum to electrically isolating aluminum oxide. In the established processes in which anodizing of aluminum is used for aluminum structuring, masks are used to achieve local anodized areas. In order to make the contact separation process by anodizing more economic, several in-situ anodizing processes either using structured processing units or printing techniques are developed and tested.